Integrating Tam and Islamic Work Ethics to Explain AI Adoption in Digital Marketing of Halal Msmes in Indonesia - Ricka Handayani; Ahmad Afandi (Yayasan Darussalam Bengkulu, 2026)
Background: This study aims to analyze the factors influencing the Adoption of Artificial Intelligence (AI) in digital marketing in halal MSMEs in Indonesia. The research focuses on understanding how perceptions of Usability, Islamic work ethics, market pressures, and technological readiness shape attitudes toward adoption, which in turn influence intentions to adopt AI. Method: The research approach is a quantitative, descriptive study involving 280 halal MSMEs active in digital marketing. The analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the direct and indirect relationships between variables, including the mediating role of attitudes towards adoption. Results: The study found that all tested factors had a positive effect on attitudes towards AI adoption. Attitudes toward adoption have been shown to mediate the relationship between these factors and adoption intentions. These findings confirm that fostering a positive attitude is key to encouraging MSMEs' intention to adopt AI. The study's results emphasize the importance of increasing perceptions of benefits, ease of use, alignment with ethical values, responsiveness to the market, and technological readiness to drive AI adoption. Governments, technology providers, and religious institutions can support MSMEs by providing user-friendly AI training, guidance, and solutions to strengthen adoption-readiness. Conclusion: This study contributes to the literature on technology adoption in MSMEs by integrating cultural, ethical, and market pressure factors, as well as emphasizing the role of attitude mediation in shaping AI adoption intentions in the context of halal business.